Estrategias del juego para el aprendizaje significativo en niños y niñas de primer grado de educación general básica de la escuela Mi Sendero de la parroquia La Providencia de la ciudad de Machala provincia de El Oro 2014 - 2015. - Añazco Vélez, Jéssica Susana (2015)
The game is the vital activity of the human being, that he has been present from childhood in the familiar, social and cultural space. Popularly it is identified with fun,